Martian dayside magnetic topology and structures of the cross-terminator magnetic loops – multispecies magnetohydrodynamic simulations. Issue 2 (24th February 2023) - Li, Guokan; Lu, Haoyu; Li, Yun; Cao, Jinbin; Li, Shibang
ABSTRACT: The interaction between impinging magnetized solar wind and Martian crustal fields produces complexly distributed magnetic topologies in the dayside magnetosphere. This study focused on obtaining the distribution of Martian dayside magnetic topology and the structures of the cross-terminator magnetic loops. A 3D multispecies magnetohydrodynamic model was employed to simulate the interactions between Mars and solar winds, and a 110° spherical harmonic model was used to calculate the crustal fields. We randomly extracted more than 1000 magnetic field lines from the near-Mars region of the model results. These results indicate the existence of large-scale closed fields and high-inclination-angle open fields in the Southern hemisphere, exerting their influence even above the height of the ionopause, resulting in a complex relationship between plasma motion and magnetic topology distribution. In contrast, the plasma motion patterns in the Northern hemisphere are similar to those observed in unmagnetized planets. Furthermore, the model results show two types of cross-terminator magnetic loop. Small-scale cross-terminator magnetic loops connect the local atmosphere on the dayside and nightside, whereas many large-scale magnetic loops cross the centre–tail region and extend more than 2 R M downstream of Mars, especially in the Southern hemisphere. Finally, the clock angle distribution shows magnetic field distortion at 1000 km altitude. This study provides a clearer and more detailed description of the Martian dayside magnetic topology and the structures of the cross-terminator magnetic loops.